Deauthorizing Fatwa on Money Politics: Shifting Religious Morals in the Era of Transactional Democracy - Muhammad Wahdini; Muhammad Torieq Abdillah; Hamzah, Alya Aulia Rachman (MUI Sulawesi Selatan, 2025)
The recurring phenomenon of money politics in every electoral contest in Indonesia reflects a persistent tension between religious moral authority and electoral political rationality. Although Nahdlatul Ulama (NU), Muhammadiyah, and the Indonesian Ulema Council (MUI) have issued fatwa forbidding money politics as a form of risywah (bribery) that contradicts Islamic principles of justice and trustworthiness, the practice continues to thrive at the grassroots level. Therefore, this study aims to investigate why the fatwa on money politics issued by major Islamic institutions in Indonesia have been ineffective in shaping the political behavior of the ummah in the Reformasi era. A qualitative method framed within the sociology of fatwa and the politics of Islamic law was used. This combined analytical perspective was used to examine fatwa as both normative-legal texts and socio-political instruments. Data were collected from fatwa documents, organizational publications, as well as elite and community responses to the practice of money politics. The results showed a process of deauthorization of fatwa, namely the weakening of religious moral authority under the growing dominance of transactional democratic logic and pragmatic electoral rationality. In this context, fatwa function more as symbolic moral references than effective instruments capable of transforming political behavior. The results underscore the need to reorient religious authority from a purely normative approach toward an ethical-political praxis that is more responsive to contemporary socio-political realities. In conclusion, this study contributes theoretically by expanding the understanding of the relationship between religion and politics in Indonesia and enriching scholarly discussions on the effectiveness of fatwa within the modern democratic sphere.